Development of Leading Commodities for Vegetable and Fruit Crops in Brebes Regency, Central Java - Aminda, Fadilla Ristya; Sari, Ayu Kumala; Anggrasari, Herdiana (West Science Interdisciplinary Studies, 2024)
Determining leading commodities is very important to increase regional competitiveness in economic development. This research aims to identify leading commodities for vegetable and fruit crops in the Brebes Regency, analyze the continuity of leading commodities, and determine the pattern and structure of leading commodities. The research uses a quantitative approach with secondary data for 2018-2022. Data were analyzed using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology analysis methods. The analysis results show that Brebes Regency's leading commodities for vegetable and fruit crops are shallot, rose apple, mango, banana, sapodilla, breadfruit, apple, melinjo, and twisted cluster bean. Potential commodities that have the opportunity to become leading commodities in the future are welch onion, yard long bean, chilli, cayenne pepper, tomato, eggplant, green bean, chayote, duku, guava, tangerine, mangosteen, pineapple, papaya, rambutan, salacca, grape, and jengkol. The pattern and structure of vegetable and fruit crops in Brebes Regency, which is considered advanced and fast-growing, is shallots. Plants with fast-growing patterns and structures are garlic, Welsh onion, cabbage, yard long bean, chili, cayenne pepper, tomato, eggplant, green bean, cucumber, chayote, water spinach, melon, watermelon, star fruit, duku, durian, rose apple, tangerine, mangosteen, pineapple, papaya, banana, grape, and jengkol.